(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Magnetic materials play significant role in developing science and technology. Due to their innovative features and applications in different fields, magnetic nanoparticles are in high demand recently. Due to their promising applications in various fields like electronics, optics, ceramics, high-density magnetic storage devices, tumour-targeted drug delivery systems, contrast enhancers for magnetic resonance imaging, transformer cores, catalysis, biomedicine, etc., spinel ferrite nanoparticles attract significant interest. This paper reflects critical study of Ferromagnetic materials.